Żołnierze a dzikie i obce zwierzęta na linii frontu wojennego w ujęciu autorów antycznych - Kostuch, Lucyna (Studia Europaea Gnesnensia, 2019)
The aim of this paper is to analyze antique testimonies documenting the relationships between soldiers and the wild and strange animals that armies encountered on the march, in military camps, on the battlefield and during clashes at sea. Also, the author attempts to discuss the numerous problems of reconstructing such relationships. The wild and strange beasts on the frontline drew the attention of writers for several reasons: they were attributed the role of divine omens, and therefore their spontaneous appearance may have had an impact on the course of military action; when soldiers saw an animal of a particular species, things were discussed; one would also describe the animals the soldiers observed, hunted, or played with. Thus the paper highlights one of the aspects in the daily life of soldiers of the Greco-Roman world. In a broader sense, the study combines historical research with ethological inquiry.